Correction factor determination on failure rate equation of MacLaurin series for low and high mode application - Biyanto, T.R. (Ain Shams University, 2016)
Safety Instrumented Function (SIF) is implemented on the system to prevent hazard in process industry. In general, most of SIF implementation in process industry works in low demand condition. Safety valuation of SIF that works in low demand can be solved by using quantitative method. The quantitative method is a simplified exponential equation form of MacLaurin series, which can be called simplified equation. Simplified equation used in high demand condition will generate a higher Safety Integrity Level (SIL) and it will affect the higher safety cost. Therefore, the value of low or high demand rate limit should be determined to prevent it. The result of this research is a first order equation that can fix the error of SIL, which arises from the usage of simplified equation, without looking the demand rate limit for low and high demand. This equation is applied for SIL determination on SIF with 1oo1 vote. The new equation from this research is Î»Â =Â 0.9428 Î»MCÂ +Â 1.062Eâ04 H/P, with 5 average of error, where Î»MC is a value of Î» from the simplified equation, Hazardous event frequency (H) is a probabilistic frequency of hazard event and P is Probability of Failure on Demand (PFD) in Independent Protection Layers (IPLs). The equation generated from this research could correct SIL of SIF in various H and P. Therefore, SIL design problem could be solved and it provides an appropriate SIL. Â© 2016 Faculty of Engineering, Ain Shams University